Randomized clinical studies of the benefits and limitations of Irradiation Laser Intravenous of Blood (ILIB) in Dentistry: an integrative review (Research, Society and Development, 2021)
The objective of this work is to answer the guiding question "what are the effects of blood irradiation intravenously in dentistry?". For this, a more targeted and in-depth search was performed on the Cochrane, SciELO, PubMed and Scopus platforms through the descriptors Low level laser; photobiomodulation; dentistry, which sought to integrate the words “and” and “more” in order to select articles with the content described above. Finally, after the fulfillment of the eligibility criteria, six articles were selected, composed in the period from 2016 to November 2020, to carry out a more in-depth analysis. As this subject is something new, however, it is known many studies have been published in Russia, but without an English translation. Thus, after reading the selected articles, it could be observed that the application of low-level laser with dosimetry and adopted suggestions is extremely beneficial, but its use still needs further studies due to the side effects that may arise, which demonstrates the presence of positive and negative factors in the use of this technique, mainly in dental use. The limitation of this study is in identifying the descriptors in the DECs and finding articles in English and other more common ones, making it necessary that studies continue to be carried out and published, so that subjects like this are disseminated to the population.